Numerical Compensation Method for Measuring Error of Tooth Profile of ZC1 Worm on Shaft Section - Zhiqiang Zhu; Jie Tang; Zhaoyao Shi (Jixie chuandong)
According to the mathematical model of ZC1 worm shaft section tooth profile，the theoretical discrete points of worm shaft section tooth profile can be obtained. In the coordinate measurement of ZC1 worm shaft section tooth profile，the principle error is introduced due to the misalignment of x axis. Therefore，the tooth profile theoretical contact points close to the actual contact points are solved by subdivision method，Newton interpolation method and cubic spline interpolation method，and the compensated tooth profile deviation can be obtained. Taking the ZC1 worm with modulus of 4 mm as an example，compared with the evaluation results of the total deviation of the tooth profile without compensation，the total deviation results of the compensated tooth profile obtained by subdivision method，third-order Newton interpolation method and cubic spline method are close to the total deviation of the normal tooth profile obtained from the same specimen at the P26 gear measuring center in Klingelnberg，Germany. The compensation method has obvious effect and presents certain universality in contact precision measurement.